(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2023)
This research aims to analyze the effectiveness of implementing the e-blud application system at the Tampojung Pregi Community Health Center, Waru sub-district, Pamekasan district. Effectiveness is defined as the level of program achievement compared to predetermined targets. using observational data collection methods and interviews with the head of the community health center and the section that handles financial reporting at the community health center. In this study, researchers used several benchmarks, namely program success, target success, satisfaction with the program, level of input output and overall goal achievement, in order to measure the level of effectiveness of implementing the e-blud application at the Tampojung Pregi Community Health Center. The results of the research show that the implementation of the application system e-blud at the Tampojung Pregi Community Health Center is very effective in helping with financial and non-financial work or reporting processes. Where the reporting process is easier because in the application there are several menus related to activities at the health center and the reporting process does not take long, and the reports produced are neat and precise. In implementing the e-blud application here, there are still several obstacles encountered, such as facilities and infrastructure as well as human resources, where to overcome this, the government has provided outreach and training regarding how the e-blud application works at health centers.